Associations between functional autoantibodies targeting GPCRs, antinuclear antibodies, and inflammatory cytokines TNF-α: a cross-sectional study of 19,810 individuals - Chen, Xin; Kieselbach, Brit; Krämer, Bernhard K.; von Baehr, Volker; Reichetzeder, Christoph; Hocher, Berthold (Frontiers in Immunology, 2026)
IntroductionFunctional autoantibodies targeting G protein–coupled receptors (GPCR-AAbs) have increasingly been implicated in autoimmune and inflammatory diseases. However, their relationships with established autoimmune biomarkers, such as antinuclear antibodies (ANA), and key inflammatory cytokines remain insufficiently understood. This study aimed to investigate the associations between different functional GPCR-AAbs, ANA positivity, and inflammatory cytokines, with a particular focus on potential sex-specific effects.MethodsWe conducted a cross-sectional analysis of 19,810 individuals from a large clinic-based cohort. Serum concentrations of functional GPCR-AAbs (Igβ1AR-AAb, Igβ2AR-AAb, IgM3MR-AAb, IgM4MR-AAb, IgETAR-AAb, and IgAT1R-AAb), ANA titers, and the inflammatory cytokine tumor necrosis factor-α (TNF-α) were measured. Multivariable regression models were applied to assess associations between GPCR-AAbs, ANA positivity, and TNF-α levels, adjusting for demographic and clinical covariates, including age. Sex-stratified analyses were performed.ResultsMultiple GPCR-AAbs were significantly associated with ANA positivity, including Igβ1AR-AAb, Igβ2AR-AAb, IgM3MR-AAb, IgM4MR-AAb, IgETAR-AAb, and IgAT1R-AAb. These associations remained robust after adjustment for age and were more pronounced in females. In women, IgM4MR-AAb levels were independently associated with higher TNF-α concentrations (standardized coefficient = 0.28, p = 0.004). No significant associations between GPCR-AAbs and TNF-α were observed in men after age adjustment.DiscussionThis large-scale cross-sectional study identifies a selective inflammatory axis linking ANA, TNF-α, and functional GPCR-AAbs—particularly M4 muscarinic receptor autoantibodies—in a sex-specific manner. These findings suggest that GPCR-AAbs may complement ANA as early biomarkers of immune dysregulation and provide novel mechanistic insights into autoimmune activation. GPCR-AAbs may hold clinical relevance for risk stratification and therapeutic targeting in autoimmune diseases.